Outcome of late term pregnancy in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Azman, Siti Fatimah Abd. (2020)
Objective: Late term pregnancy is associated with an increased risk of morbidity towards parturient and fetus. This study aims to address the number of cases and outcome of maternal and perinatal morbidity in late term pregnancy. Methodology: This was a retrospective study, a review of intended studied pregnancy at 41 weeks involving 324 patients who delivered at late term in the past five years at HUSM. Data involving socio-demographic of the patients, method of induction, mode of delivery, the outcome of delivery as well as maternal and fetal complications were recorded and analysed. Results: The number of cases of late term pregnancy was 8.73%. Out of 324 patients, 144 of them (44.4%) were induced into labour. There were 269 patients (83%) delivered via spontaneous vertex delivery, 12 patients (3.7%) via operative vaginal delivery and 43 patients (13.3%) via lower segment Caeserean section. The incidence of postpartum hemorrhage and perineal trauma were 4.9% and 0.6% respectively. In terms of fetal outcomes, 6.5% was admitted to neonatal intensive care unit following delivery, and 2.5% had their Apgar score of less than 7 at 5 minutes. There was a significant association between mode of delivery and fetal outcome (neonatal intensive care unit admission and poor Apgar score at 5 minutes) with higher incidences found in patients delivered via operative vaginal delivery. Mothers who delivered via operative vaginal delivery were more likely to have baby admitted to NICU and Apgar score less than 7 with the odd ratio 9.11(95% Cl:2.44,33.93) and 17.6(95% CI:3.63,85.28) respectively. Conclusion: Our study found that the number of cases of maternal and perinatal morbidity in late term pregnancy was lower compared to previously reported figures from other studies.